Pengaruh Whistleblowing dan Penerapan Hukum Karma Phala Pada Pencegahan Kecurangan di LPD Se-Kota Denpasar - Ni Ketut Muliati; Ni Wayan Yuniasih; Putu Deddy Samtika Putra (Juara: Jurnal Riset Akuntansi, 2021)
Fraud is a problem that is often faced, one of which is the Village Credit Institution. This study wants to examine the effect of whistleblowing and the application of the law of karma phala on fraud prevention. This research was conducted on 34 LPDs in Denpasar City. Research respondents used 84 LPD employees who were determined by the non-probability sampling method. Multiple regression analysis is used to test the research hypothesis. The results showed that whistleblowing and the application of the law of karma phala had a positive effect on fraud prevention in the Denpasar City LPD. KNKG (2008) states that the effectiveness of whistleblowing will increase the participation of the community and company employees to dare to act in the context of preventing fraud and corruption by reporting to the authorities. Individuals who believe in the law of karma phala will avoid unlawful acts.